Active surveillance of highly suspicious thyroid nodules cohort in China shows a worse psychological status in younger patients - Liu, Chunhao; Zhao, Hao; Xia, Yu; Cao, Yue; Zhang, Liyang; Zhao, Ya; Gao, Luying; Liu, Ruifeng; Liu, Yuewu; Liu, Hongfeng; Meng, Zhilan; Liu, Shuzhou; et al. (Frontiers in Oncology, 2022)
Background: Active surveillance has been considered a safe alternative to surgery for low-risk papillary thyroid microcarcinoma. This study aimed to assess the oncological outcomes and psychological status of active surveillance of highly suspicious thyroid nodules ≤10 mm in China. Methods: This prospective single-center cohort study enrolled 336 patients with highly suspicious thyroid nodules for active surveillance to assess oncological outcomes and psychological status. The psychological status of patients was assessed by two different questionnaires and compared among different patient groups. Results: During a median follow-up period of 28.5 months, eight patients underwent delayed surgery for tumor enlargement and one for lymph node metastases. The cumulative incidence of disease progression at 5 and 10 years was 6.0% and 12.8%, respectively. Patients who underwent delayed surgery had no permanent complications, and no patient had distant metastasis or death. Patients ≤30 years old had a higher baseline anxiety score (4.9 vs. 3.8, p=0.024), a higher proportion of baseline anxiety score, i.e., ≥8 points (24.0% vs. 12.6%, p=0.033), and a worse baseline emotional function (62.7 vs. 70.7, p=0.013) than patients >30. During AS, patients ≤30 years of age had higher overall anxiety levels (p=0.005) and a worse overall emotional function (p=0.001). Conclusions: Active surveillance in Chinese patients with highly suspicious subcentimetre thyroid nodules has good oncological outcomes and can be used as a safe alternative to surgery. Younger patients (≤30) show a worse psychological status; therefore, more attention should be paid to younger patients.